Determinants of reliability of financial statements of school operational grants in Indonesian: the mediating role of contextual variables / Ari Kuncara Widagdo , Payamta and Dhony Prastyo Nugroho - Widagdo, Ari Kuncara; Payamta, Payamta; Nugroho, Dhony Prastyo (Universiti Teknologi MARA, Shah Alam: Accounting Research Institute (ARI), 2019)
This study aimed to examine the effect of principal support on the reliability of financial statements of School Operational Grants (Bantuan Operasional Sekolah or BOS) and to examine the mediation role of quality human resource, governance and internal control. The sample of this study consisted of 120 treasurers of BOS in Ponorogo District. This study employed the structural equation model, namely the Partial Least Square (PLS), to analyse the data. The results indicate that principal support affects the reliability of the financial statements of the BOS. Besides, quality human resource, governance and internal control partially mediate the relation between principal support and the reliability of the financial statements of the BOS.